การผลิตไฮโดรเจนจากกลีเซอรอลโดย การรีฟอร์มมิงด้วยไอน้ำผ่านตัวเร่งปฏิกิริยาแพลเลเดียม บนตัวรองรับแท่งอะลูมินา - อภัสราภรณ์ เจียวก๊ก (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
Production of hydrogen gas from steam reforming of glycerol using tubular reactor was studied here, feed with pure glycerol and crude glycerol from biodiesel production process. The objective was to study suitable condition of the reaction. The studied parameters were reaction temperature, catalyst loading, feed concentration of glycerol, number of catalyst tubes, steam/carbon ratio and contact time. The analysis of results showed that the percentage of carbon and hydrogen input converted into gas products. The results showed that the conversion of carbon and hydrogen input increased with the increase of the reaction temperature from 600 to 800 °C. The distribution of gas product was found that, when the reaction temperature increased, the conversion to H₂ and CO gases increased while the conversion to CO₂and CH₄ gases decreased. The palladium loading, 1.0 %wt Pd/Al₂O₃ catalyst at the reaction temperature of 800 ºC and 7 tubes exhibited the highest reforming activity that was the suitable reaction condition for hydrogen production. Hydrogen and carbon conversion were 93.55 and 86.66 %, respectively. At glycerol concentration at 5000 ppm 1.0% wt and 4 tubes of Pd catalyst, when the rise of the S/C ratio from 1:1 to 3:1 and the contact time from 1 to 2 s led to the increase of hydrogen and carbon conversion. The comparison of crude glycerol and pure glycerol was indicated that crude glycerol converted to gas product more than pure glycerol in the same condition. From these results, the steam reforming process can be considered as a potential method for H₂ production from the crude glycerol. It is not only increasing the alternative energy as clean energy but also promoting the waste management from biodiesel process.